ANALISIS PENILAIAN KINERJA KEUANGAN PEMERINTAH DAERAH: Studi Kasus pada Pemerintah Daerah Kabupaten Sleman Tahun 2017 - 2019 - Ruddy Tri Santoso; Muhammad Syukri; Ni'matul Hasanah (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This research aims to measure the independence of local governments in implementing regional autonomy in Sleman Regency by assessing the financial performance of the Regional Financial and Asset Agency (BKAD) based on the Budget Realization Report (LRA) for 3 years from 2017 - 2019 by analyzing the effectiveness ratio of Regional Original Income, growth ratio, compatibility ratio, regional financial independence ratio, and regional financial dependency ratio. The results of the analysis showed that the growth ratio of Regional Native Income (PAD) was assessed to have a positive growth rate. PAD effectiveness level is already very effective with an average effectiveness of 110.5%. Ratio of Compatibility has decreased in 2019 to 81.47% which shows that still local governments still allocate a lot of operating spending rather than capital expenditure. The independence ratio in the Sleman Regency government increased from 51.50% to 54.36% which was categorized as having moderate financial capabilities and showing participatory relationship patterns. The level of local financial dependence on the central government is considered very high reaching 63.99%. This shows that the Sleman County Regional Government has not been able to maximize Local Original Income effectively and efficiently in obtaining Regional Revenue.